Attenuated cardiovascular response to sympathetic system activation during exercise in patients with dialysis-induced hypotension - Fotbolcu, Hakan; Duman, Dursun; Alışır Ecder, Sebahat; Oduncu, Vecih; Çevik, Cihan; Tigen, Kürşat; Şirin, Gökçe; Özker, Emre; Kıran, Burak; Başaran, Yelda (Karger, 2011)
Background: We wished to investigate potential causes of dialysis-induced hypotension (DIH), including the attenuated cardiovascular response to sympathetic system activation during exercise and myocardial dysfunction. Methods: This study included 26 end-stage renal disease (ESRD) patients with DIH, 30 ESRD patients without DIH (Non-DIH), and 30 control subjects. Each patient was evaluated with echocardiography and a symptom-limited treadmill stress test. The chronotropic index (CRI), heart rate recovery (HRR), systolic blood pressure response to exercise (SBP response), and tissue Doppler systolic myocardial velocities were calculated. Results: The HRR and velocities were reduced in dialysis patients compared to controls; however, they were similar in patients with and without DIH. Patients with DIH had the lowest CRI compared to theNon-DIH group (0.62 ± 0.15 vs. 0.73 ± 0.17, p = 0.020) and controls (0.62 ± 0.15 vs. 0.86 ± 0.11, p < 0.001). Similarly, patients with DIH had the lowest SBP response values compared to the Non-DIH (34.88 ± 15.01 vs. 55.67 ± 25.42, p = 0.002) and controls (34.88 ± 15.01 vs. 59.70 ± 23.04, p < 0.001). Conclusion: Patients with DIH have inadequate sympathetic activity of the cardiovascular system during exercise and impaired left ventricular systolic function. Both factors could contribute to the development of hypotension during hemodialysis.
Keywords: Autonomic Nervous System; Chronotropic Incompetence; Dialysis; Heart Rate Recovery; Hypotension; Systolic Blood Pressure